2022
DOI: 10.3390/nu14234981
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gastric Microbiota and Inflammatory Cytokine Responses in Patients with Helicobacter pylori-Negative Gastric Cancer

Abstract: The role of the gastric mucosal microbiome in Helicobacter pylori-negative gastric cancer (GC) remains unclear. Therefore, we aimed to characterize the microbial alterations and host inflammatory cytokine responses in H. pylori-negative GC. Gastric mucosal samples were obtained from 137 H. pylori-negative patients with GC (n = 45) and controls (chronic gastritis or intestinal metaplasia, n = 92). We performed 16S rRNA gene sequencing (n = 67), a quantitative reverse transcription-polymerase chain reaction to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Moreover, IL1B, IL6, and CXCL8 have been proven to regulate the association between chronic HP infection and the process of GC. A previous study reported that CXCL2 was a common gene between HP infection and spontaneous intracerebral hemorrhage [24][25][26][27][28]. In our study, CXCL1, CXCL2, and CXCL8 were upregulated in the group with HP infection.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, IL1B, IL6, and CXCL8 have been proven to regulate the association between chronic HP infection and the process of GC. A previous study reported that CXCL2 was a common gene between HP infection and spontaneous intracerebral hemorrhage [24][25][26][27][28]. In our study, CXCL1, CXCL2, and CXCL8 were upregulated in the group with HP infection.…”
Section: Discussionsupporting
confidence: 66%
“…Fourteen studies reported on people infected with Helicobacter pylori . A total of 25 studies collected samples from gastric mucosal biopsies during gastroscopy, while four studies used fecal samples ( Liang et al, 2019 ; Qi et al, 2019 ; He et al, 2022 ; Kim et al, 2022 ), and four studies used gastric juice samples ( Park et al, 2022 ; Sun et al, 2022 ; Peng et al, 2023 ; Wei et al, 2023 ). Twenty-seven studies used 16S gene sequencing technology, but with different amplified regions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has indicated a decrease in Haemophilus in the oral microbiome of individuals with GC, as well as a reduction in the presence of Haemophilus parain uenzae in GC [30]. Nevertheless, a different study indicated a rise in the prevalence of Haemophilus in GC [31], potentially linked to their connection with functional dyspepsia in the control group rather than intestinal metaplasia in the control group [29]. These results indicate that the Haemophilus has different effects on GC at different stages, and our study showed that the Haemophilus has a certain promoting effect on GC.…”
Section: Discussionmentioning
confidence: 94%
“…Due to its ability to reduce nitrates, the presence of Haemophilus may play a role in the ongoing in ammation process [28]. And it has also been shown that a negative relationship between the levels of Haemophilus and IL-1B mRNA [29]. Previous research has indicated a decrease in Haemophilus in the oral microbiome of individuals with GC, as well as a reduction in the presence of Haemophilus parain uenzae in GC [30].…”
Section: Discussionmentioning
confidence: 99%